"The Gatekeepers in Prevention": Community Pharmacist Perceptions of Their Role in the Opioid Epidemic. Issue 1 (December 2022) - Vadiei, Nina; Eldridge, Lori Ann; Meyerson, Beth E.; Agley, Jon
Background : Community pharmacists are at the frontline of patient care, yet their role in the opioid epidemic remains unclear. This qualitative study examines the perception of community pharmacists about their role in the opioid epidemic and challenges to fulfilling this role. Methods: A secondary analysis of cross-sectional survey data from an Indiana census of community managing pharmacists was conducted. Qualitative data were coded using a priori and emergent themes. A priori categories included the perceived role of pharmacists in the opioid epidemic and perception of practice barriers. Results: A total of 215 Indiana community managing pharmacists participated in this study. Pharmacists understood themselves as gatekeepers in preventing opioid misuse and overdose. Reported pharmacy practices included providing patient education and communicating with prescribers. Challenges to fulfilling this role included pharmacy structure and operation, lack of patient and provider clarity about pharmacist scope of practice, and pharmacist perception that that there is no available discretionary time to support additional services. Conclusion: Pharmacists believe they have a vital role in combatting opioid misuse and overdose but are hampered by structural aspects of pharmacy practice and lack of recognition of their role. Pharmacy associations and policy partners are encouraged to identify opportunities to address these barriers.